2001
DOI: 10.1021/ci010281+
|View full text |Cite
|
Sign up to set email alerts
|

QSAR Analysis of Hypoglycemic Agents Using the Topological Indices

Abstract: The molecular topology model and discriminant analysis have been applied to the prediction of some pharmacological properties of hypoglycemic drugs using multiple regression equations with their statistical parameters. Regression analysis showed that the molecular topology model predicts these properties. The corresponding stability (cross-validation) studies performed on the selected prediction models confirmed the goodness of the fits. The method used for hypoglycemic activity selection was a linear discrimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 20 publications
(21 reference statements)
0
25
1
Order By: Relevance
“…We used the same atom properties to calculate the global topological charge index (GTCI) [50] and the eigenvalue descriptor burden modified eigenvalues (BCUT) [1]. Furthermore we calculated the Moreau -Broto autocorrelation ACðdÞ and the Radial Distribution Function (RDF) [51].…”
Section: Parameters -Vector-based Codingmentioning
confidence: 99%
“…We used the same atom properties to calculate the global topological charge index (GTCI) [50] and the eigenvalue descriptor burden modified eigenvalues (BCUT) [1]. Furthermore we calculated the Moreau -Broto autocorrelation ACðdÞ and the Radial Distribution Function (RDF) [51].…”
Section: Parameters -Vector-based Codingmentioning
confidence: 99%
“…Murcia-Soler et al [4] used molecular connectivities (a type of topological index) to model the anti-hyperglycaemic potency of 13 sulphonylurea drugs. Other workers have modelled glitazones [5][6][7][8], spirohydantoins [9,10], PTP1B inhibitors [11] and flavonoids [12].…”
Section: Introductionmentioning
confidence: 99%
“…Other workers have modelled glitazones [5][6][7][8], spirohydantoins [9,10], PTP1B inhibitors [11] and flavonoids [12]. Murcia-Soler et al [4] also used molecular connectivities to model the acute toxicity (LD 50 ) *Corresponding author. Email: j.c.dearden@ljmu.ac.uk and plasma protein-binding (%PPB) of the sulphonylurea drugs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Woo et al (2002) reported mechanism-based structure-activity relationships analysis in carcinogenic for drinking water DBPs. The QSAR analysis of hypoglycemic agents also has been conducted by using the topological indices (Murcia-Soler et al, 2001). In regards to QSAR model process and model validation, linear QSAR regression models have been studied for the prediction of bio-concentration factors by physicochemical properties, and structural theoretical molecular descriptors are studied by Papa et al (2007).…”
Section: Quantitative Structure-activity Relationship (Qsar)mentioning
confidence: 99%